2x-4+3(x-2)=0

Simple and best practice solution for 2x-4+3(x-2)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-4+3(x-2)=0 equation:


Simplifying
2x + -4 + 3(x + -2) = 0

Reorder the terms:
2x + -4 + 3(-2 + x) = 0
2x + -4 + (-2 * 3 + x * 3) = 0
2x + -4 + (-6 + 3x) = 0

Reorder the terms:
-4 + -6 + 2x + 3x = 0

Combine like terms: -4 + -6 = -10
-10 + 2x + 3x = 0

Combine like terms: 2x + 3x = 5x
-10 + 5x = 0

Solving
-10 + 5x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '10' to each side of the equation.
-10 + 10 + 5x = 0 + 10

Combine like terms: -10 + 10 = 0
0 + 5x = 0 + 10
5x = 0 + 10

Combine like terms: 0 + 10 = 10
5x = 10

Divide each side by '5'.
x = 2

Simplifying
x = 2

See similar equations:

| (9y^2+5y+2)-(2y^2-5y+9)= | | 2/3(a-2)+6=18 | | C/5=4 | | x^2+6x-97=0 | | 6(x+5)=-4x+6+2x | | 4.5/18 | | 3x-5(x+3)=2x+15 | | 5(3x-5)-7(2x+5)+9(3x-2)= | | x+5+x-2=54:15 | | x+5=54 | | (6y^2-5y+6)-(9y^2-5y+7)= | | -1.4-(0.2x+3)=0.8x-1.2 | | 4x^2+18x-1882=0 | | x+5+x-2=54-15 | | -5=x+10 | | x+5+x-2=54 | | 6(5x+4)+2(3x-7)-5(7x-4)= | | 5(2t+5)= | | x+(x*12.36/100)=450648.16 | | 3x^2+24x=0forx | | 3/4x+5/4-1/4 | | 21x+77-18x+54= | | 16^2/3 | | ln(3x^2)=8 | | N*18=126 | | -5+8-4(2y+1)= | | 18x+36+12x-21= | | 9/4x=6/2 | | 2x+15=5x+14 | | 0.7n=-77 | | 6-2b+3=1 | | 8y-13=-5(y-5) |

Equations solver categories